2013
DOI: 10.1155/2013/501284
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantification of DNA Aneuploidy by Image Cytometry as an Adjunct for the Cytologic Diagnosis of Malignant Effusion

Abstract: Abstract. DNA aneuploidy is a cancer biomarker, which may have a potential diagnostic value in body effusion specimen. DNA aneuploidy is determined by measuring the DNA content of tested cells and comparing them with diploid cells (2c). In order to assess the value of automated DNA image cytometry (DNA-ICM) in the cytologic diagnosis of effusion, we measured DNA ploidy using an automated DNA-ICM analysis system in 126 consecutive effusion specimens and followed the cases for histologic diagnosis. Half of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Therefore, the automated quantitative image analysis of DNA aneuploidy was also performed in this study, and we observed that the proportion of DNA aneuploidy in the cervical precancerous cells was much higher than that in the NUC cells but was very similar to that in the Caski cells, which was we had not expected. Some studies have shown that automated DNA ICM technology might increase the sensitivity of the cytologic detection of dysplastic and cancerous cells in several types of cancers; these cells in turn could be used as a marker of progression [18, 27]. However, the significance of DNA aneuploidy has been confined only in clinical studies in the literature and is not yet fully understood at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the automated quantitative image analysis of DNA aneuploidy was also performed in this study, and we observed that the proportion of DNA aneuploidy in the cervical precancerous cells was much higher than that in the NUC cells but was very similar to that in the Caski cells, which was we had not expected. Some studies have shown that automated DNA ICM technology might increase the sensitivity of the cytologic detection of dysplastic and cancerous cells in several types of cancers; these cells in turn could be used as a marker of progression [18, 27]. However, the significance of DNA aneuploidy has been confined only in clinical studies in the literature and is not yet fully understood at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5-10 × 10 3 cells were trypsinized with 0.25% trypsin-EDTA and pelleted by centrifugation at 1000 rpm for 5 min. The pellets were collected and fixed in PreservCyt (Heer, Wuhan, China) and were then used to generate slides using the Feulgen method under temperature-controlled conditions; these conditions were similar to those that have been reported in previous studies [18]. The SPICM-DNA system was used for the automatic classification of cells, measurement of DNA ploidy and analysis of aneuploidy, which was purchased from the Heer Company (Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%